Contemporary Middle East Art At Venice Biennale: A Study Of A Postcolonial Curatorial Strategy (2011-2019) - Fatemi, Seyedehsamaneh (2023)
The presence of Middle East art in the international arena has increased in recent decades. This increase has attracted the attention of critics, intellectuals, and curators to Middle East art more than ever. Despite the research that has been done in the field of contemporary Middle East art, the art of this region is relatively new and undiscovered in art history. This research aims to better understand the contemporary art of the Middle East specifically in the international arena. To do so this research has focused on Middle East art at the Venice Biennale during the years 2011 to 2019. This research uses thematic analysis and postcolonial discourses to study Middle East artworks at the Venice Biennale. This research investigated the prevailing themes of Middle East artworks and examined them from a postcolonial perspective. Then, the curatorial strategy of the Venice Biennale from 2011 to 2019 had been examined. The findings have shown that despite the political restrictions that the Venice Biennale follows, the dominant theme of Middle East artworks at Venice Biennale is the social and political theme. As well, postcolonial discourses and themes of artworks have common concepts.